2022
DOI: 10.21061/jvs.v8i1.308
|View full text |Cite
|
Sign up to set email alerts
|

Stranger in a Strange Land: A Qualitative Exploration of Veteranness

Abstract: Veteran identity and veteran experience are growing areas in veteran studies. Between and across these topics lives the characteristics of veteranness. This paper uses a rigorous, iterative qualitative approach to identify and understand the characteristics of veteranness as described by eight Post-9/11 veterans. The major themes were camaraderie, military "habitus", stranger in a strange land, veteran worldview, and transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A study on Vietnam veterans attending college revealed negative attitudes about students' veteran status from college officials, staff, and other college professionals, impacting the ability of these returning veterans to succeed in school (Horan, 1990). While this sentiment does not appear in recent literature, research supports student veterans still questioning the veteran friendliness of civilian peers and the potential of hostility and anti-veteran bias (Ahren et al, 2015;Gade & Wilkins, 2012;Schreger & Kimble, 2017;Young et al, 2022).…”
Section: Expansion Of Institutions Of Higher Educationmentioning
confidence: 99%
“…A study on Vietnam veterans attending college revealed negative attitudes about students' veteran status from college officials, staff, and other college professionals, impacting the ability of these returning veterans to succeed in school (Horan, 1990). While this sentiment does not appear in recent literature, research supports student veterans still questioning the veteran friendliness of civilian peers and the potential of hostility and anti-veteran bias (Ahren et al, 2015;Gade & Wilkins, 2012;Schreger & Kimble, 2017;Young et al, 2022).…”
Section: Expansion Of Institutions Of Higher Educationmentioning
confidence: 99%
“…Veterans described a sense of safety in the inherent backbone of a shared military experience where their "hybrid" sense of identity was understood in a group of peers. This hybrid identity has further been understood as a sense of "veteranness" where military veterans' definition of what being a veteran means is intertwined within sense of identity, purpose, and behaviors (Young et al, 2022). This is important in treatment services designed for military veterans because a separation between military and civilian worlds does exist.…”
Section: Trusted Social Supportmentioning
confidence: 99%
“…Scholars [75] have conceptualized "military habitus" as "unconscious thoughts and behaviors acquired through military training and service." Others [76] found that military habitus can contain useful attributes and dispositions such as going with the flow, being comfortable with discomfort, calm assertiveness, and situational awareness, among others. Along with professionally useful attributes and dispositions, military habitus can also contain "thoughts and behaviors that can impair a veteran's ability to be successful in life," such as extreme vigilance, an inability to manage emotions, and drinking alcohol, often to excess.…”
Section: Strengths Of Bac For Research With Military Undergraduates I...mentioning
confidence: 99%